Multiple Role Conflict of Working Mothers and Attitude of Exclusive Breast Milking in the New Neighborhood of the Bamboo Field, Medan Tuntangan District - Anggraini, Desi; Fitri, Sari Rahma (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2022)
Breast milk (ASI) is the most complete and natural source of food or nutrition for babies. Breastfeeding is an important activity in child care and preparation for future generations. Working mothers will encounter difficulties regarding timing between breastfeeding and work. This type of research is descriptive research, namely research or observations carried out simultaneously at one time (once). The population in this study were working mothers in the Baru Ladang Bambu Village, Medan Tuntungan District, who had 32 children aged over 6 months. The sampling technique was purposive sampling. The results of the statistical test between the dual role conflict of working mothers and the action of exclusive breastfeeding in the Baru Ladang Bambu Village, Medan Tuntungan District, obtained a correlation coefficient or r value of -0.420, the probability of 0.020 with a 95% confidence level where p <0.05. This means that there is a relationship between the dual role conflict of working mothers and the action of exclusive breastfeeding in the Baru Ladang Bambu Village, Medan Tuntungan District. It is hoped that mothers will increase their knowledge about exclusive breastfeeding even while working, either through mass media or asking health workers.